Stress Hormones Bring Birds, Pathogens and Mosquitoes Together. Issue 5 (May 2017) - Dhondt, André A.; Dobson, Andrew P.
Abstract : Do stress hormones, such as corticosterone, enhance bird susceptibility to mosquitoes in ways that enhance rates of co-infection? Does this then enhance pathogen emergence?